Experimental evaluation of optimum process parameters for spinning of metals - FEYZİOĞLU, AHMET (CARL HANSER VERLAG, 2018)
During the shear forming process, precision, repeatability and reproducibility are significant factors to be considered while rotating the workpiece to shape it in the form of the mandrel. Final thickness of the material is dependent on the initial thickness and mandrel angle. The projected area of the final product is nearly equal to the area of the initial workpiece. On the other hand, high feed ratios may lead to cracking and low feed ratios reduce the workability and thickness of the material by causing overexpansion of the material in the radial direction. As the spinning ratio increases, the process becomes difficult. If the process is not carried out cautiously, some defects, such as wrinkling, tearing or cracking, may occur in the spun part. These are caused by applying unacceptable feeds and rpms to the material and diameter. Problems such as wrinkling, tearing or cracking can be addressed by applying the optimum rpm and velocity values with respect to the material being worked on. Several methods have been used to predict the behavior of the material during spinning. For example, during shear spinning, the surface roughness and required force can be determined by regression analysis. In this study, the correlation among optimum rpm, velocity, mandrel angle, and the initial and final thicknesses of metals during shear formation was evaluated.
Keywords: Shear forming; rotational speed; mandrel angle; metallic materials; optimum thickness; SHEAR; FORCE